2022
DOI: 10.1093/hr/uhac078
|View full text |Cite
|
Sign up to set email alerts
|

Breeding an underutilized fruit crop: a long-term program for Hylocereus

Abstract: This review describes three decades of introduction, agro-technology development, breeding and selection of Hylocereus species, known as pitaya or dragon fruit, as an example of a holistic program aimed to develop the horticultural potential of a perennial underutilized fruit crop. Interspecific homoploid and interploid crosses and embryo rescue procedures produced improved hybrids, some of which have been released to farmers. Molecular tools and morphological and phenological comparisons between the parental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 79 publications
(156 reference statements)
1
12
0
Order By: Relevance
“…The importance of the cultivation of S. megalanthus for their commercialization has allowed for the development of a wide variety of studies about the quality of the fruit, commercialization, nutritional composition, cultivation, phenology, organic fertilization, physical chemistry, genetics, postharvest management, morphology and production systems (Tel-Zur, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the cultivation of S. megalanthus for their commercialization has allowed for the development of a wide variety of studies about the quality of the fruit, commercialization, nutritional composition, cultivation, phenology, organic fertilization, physical chemistry, genetics, postharvest management, morphology and production systems (Tel-Zur, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, even today, it is difficult to clearly identify the species and varieties of dragon fruit, due to its high rate of inter-and intra-specific hybridization and the genotype-environment interaction that has led to some confusion at the national level taxonomic worldwide (Tel-Zur, 2022). The phenotypic and genetic variability in morphological characteristics associated with the plant such as height, width ribs of the cladode, distance between areoles, number of sprouts, length of the spines and sweetness, size and color of the fruit are the product of this natural hybridization process (Tel-Zur et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…megalanthus ) is a tetraploid species, having 2 n = 4 x = 44 chromosomes. This evidences the genetic proximity between all pitayas and justifies the possibility of performing interspecific homoploid crosses (2 n × 2 n ) to obtain diploid hybrids [ 11 , 69 , 70 ].…”
Section: Genetics Xenia and Metaxeniamentioning
confidence: 77%
“…Cactoideae subfamily comprises epiphytic, hemiepiphyte and climbing cacti, but the genera within this subfamily are poorly defined and there is not a consensus among taxonomists. Recent studies, based on molecular markers, have shown that genus Hylocereus (A. Berger) Britton and Rose, which includes most cultivated pitayas, should be grouped in the genus Selenicereus (A. Berger) Britton and Rose [ 20 ]; however, prestigious researchers specializing in pitaya genetics continue to distinguish the two genera separately [ 11 ]. This has negative implications, as identical plants are referred to with different scientific names, confusing readers (researchers, agronomists and farmers).…”
Section: Taxonomy and Botanymentioning
confidence: 99%
See 1 more Smart Citation